The Effect of Shallot Peel (Allium ascalonicum L.) as a Natural Growth Regulatory Substance on Root Growth of Cassava Stem Cuttings (Manihot utilissima) - Septiani Ayda; Agus Ramdani; I Gde Mertha (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The effect of shallot peel (Allium ascalonicum L.) as a natural growth regulatory substance on root growth of cassava stem cuttings (Manihot utilissima). This study aims to determine the effect of shallot peel extract on root growth of cassava stem cuttings and determine the most effective treatment for root growth of cassava stem cuttings. This study used a completely randomized design consisting of 1 factor, namely the treatment of shallot peel extract concentration which had 10 levels (concentration 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80 %, 90% and 100% of shallot peel extract) and 3 replicates. The variables observed in this study were the number of roots and the longest root length from the roots of cassava stem cuttings. The data obtained were analyzed using the ANOVA test and the HSD (Honestly Significance Different) follow-up test with an error rate of 5%. The results showed that the treatment of shallot peel extract had a significant effect on the root growth of cassava stem cuttings. The most effective concenstration of shallot peel for root number growth was 20%, while for root length growth the most effective concentration was 30%.